Codelivery of Infusion Decellularized Skeletal Muscle with Minced Muscle Autografts Improved Recovery from Volumetric Muscle Loss Injury in a Rat Model - Kasukonis, Benjamin (Tissue Eng Part A, 2016)
Skeletal muscle is capable of robust self-repair following mild trauma, yet in cases of traumatic volumetric muscle loss (VML), where more than 20% of a muscle's mass is lost, this capacity is overwhelmed. Current autogenic whole muscle transfer techniques are imperfect, which has motivated the exploration of implantable scaffolding strategies. In this study, the use of an allogeneic decellularized skeletal muscle (DSM) scaffold with and without the addition of minced muscle (MM) autograft tissue was explored as a repair strategy using a lower-limb VML injury model (n = 8/sample group). We found that the repair of VML injuries using DSM + MM scaffolds significantly increased recovery of peak contractile force (81 ± 3% of normal contralateral muscle) compared to unrepaired VML controls (62 ± 4%). Similar significant improvements were measured for restoration of muscle mass (88 ± 3%) in response to DSM + MM repair compared to unrepaired VML controls (79 ± 3%). Histological findings revealed a marked decrease in collagen dense repair tissue formation both at and away from the implant site for DSM + MM repaired muscles. The addition of MM to DSM significantly increased MyoD expression, compared to isolated DSM treatment (21-fold increase) and unrepaired VML (37-fold) controls. These findings support the further exploration of both DSM and MM as promising strategies for the repair of VML injury.